Macau, World Capital for Gambling: A Longitudinal Study of a Youth Program Designed to Instill Positive Values - Luk, Andrew L.; Chan, W U.; Hu, Sydney X. (Frontiers in Public Health, 2013)
Macau, world capital for gambling: A longitudinal study of a youth program designed to instil positive values ABSTRACT This study investigated the effectiveness of a positive youth development program for Chinese Secondary 3 students in two schools, who had been followed up since their entry to Secondary 1. A mixed research method was carried out using a pre- and post-test pre-experimental design and a focus group for the participants. The subjective outcome evaluations included participants’ perceptions of the program, program instructors, benefits of the program and overall satisfaction, and were positive. The longitudinal data from the objective outcome evaluation showed some notable improvements, and the overall effect of the program was also found to be positive for newcomers in the junior secondary years. The focus group interviews revealed mostly positive feedback in terms of the students’ general impressions of the program, with the majority of participants perceiving benefits to themselves from the program. The findings offer positive evidence of the effectiveness of the program. KEYWORDS: adolescents, positive youth development, objective outcome evaluation, subjective outcome evaluation